2021
DOI: 10.55133/eji.280421
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Helicobacter pylori seropositivity and activity on disease outcome in patients with rheumatoid arthritis, systemic lupus erythematosus and ankylosing spondylitis

Abstract: The association between infection with Gram-negative bacteria and autoimmune diseases has been investigated with controversies about the role of the organisms especially, Helicobacter pylori (H. pylori). To evaluate the impact of the presence and activity of H. pylori on the disease activity in patients with rheumatoid arthritis (RA), systemic lupus erythematosus (SLE) and ankylosing spondylitis (AS). This study was carried out on one hundred adult patients and 50 controls. Patients included 40 RA, 40 SLE, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Hamed et al investigated the effects of H. pylori ’s existence and activity on RA disease activity. According to their results, patients with active RA (DAS-28 > 3.2) showed a higher positive rate of H. pylori stool antigen than patients in remission 29 . Ebrahimia et al showed that RA patients who were H. pylori CagA-positive tended to have severe clinical manifestations with higher DAS-28 scores and higher mean VAS scores than CagA-negative patients.…”
Section: Discussionmentioning
confidence: 99%
“…Hamed et al investigated the effects of H. pylori ’s existence and activity on RA disease activity. According to their results, patients with active RA (DAS-28 > 3.2) showed a higher positive rate of H. pylori stool antigen than patients in remission 29 . Ebrahimia et al showed that RA patients who were H. pylori CagA-positive tended to have severe clinical manifestations with higher DAS-28 scores and higher mean VAS scores than CagA-negative patients.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was calculated using the WHO sample size calculator by using the population prevalence of H-pylori infection in patients of RA as 30%. 7 This is an Open Access article distributed under the terms of the Creative Commons Attribution License (https://creativecommons.org/licenses/by-nc/4.0/), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.…”
Section: Methodsmentioning
confidence: 99%
“…All participating patients were diagnosed as RA patients based on the 2010 revised criteria of the American College of Rheumatology for the classification of RA. 7 For classification purposes, a patient has to satisfy at least four of the seven criteria to be considered to have RA. Six weeks is the minimum duration for symptoms of criteria.…”
Section: Methodsmentioning
confidence: 99%
“…Many autoimmune disorders such as systemic lupus erythematosus, polymyositis, dermatomyositis, and rheumatoid arthritis have been connected with chronic urticaria (23). In this regard, H. pylori infection and/or MetS are linked to such disorders as systemic lupus erythematosus and rheumatoid arthritis (24)(25)(26)(27). MCs also contribute to the pathophysiology of these autoimmune disorders (26,28).…”
Section: Introductionmentioning
confidence: 99%